Gene and species trees of a Neotropical group of treefrogs: Genetic diversification in the Brazilian Atlantic Forest and the origin of a polyploid species - Brunes, Tuliana O. [UNESP]; Sequeira, Fernando; Haddad, Celio Fernando Baptista [UNESP]; Alexandrino, Joao [UNESP] (Academic Press Inc. Elsevier B.V., 2010)
The Neotropical Phyllomedusa burmeisteri treefrog group includes four diploid (P. bahiana, P. burmeisteri, P. distincta and P. iheringii) and one tetraploid (P. tetraploidea) forms. Here we use mitochondrial and nuclear sequence variation from across its range to verify if recognized morphospecies correspond to phylogenetic clades, examine the origin of the polyploid P. tetraploidea, and compare range wide patterns of diversification to those of other BAF organisms. We compared single gene trees with one Bayesian multi-gene tree, and one Bayesian species tree inferred under a coalescent framework. Our mtDNA phylogenetic analyses showed that P. bahiana, P. burmeisteri and P. iheringii correspond to monophyletic clades, while P. distincta and P. tetraploidea were paraphyletic. The nuclear gene trees were concordant in revealing two moderately supported groups including (i) P. bahiana and P. burmeisteri (northern species) and (ii) P. distincta, P. tetraploidea and P. iheringii (southern species). The multi-gene tree and the species tree retrieved similar topologies, giving high support to the northern and southern clades, and to the sister-taxa relationship between P. tetraploidea and P. distincta. Estimates of 'MRCA suggest a major split within the P. burmeisteri group at approximate to 5 Myr (between northern and southern groups), while the main clades were originated between approximate to 0.4 and 2.5 Myr, spanning the late Pliocene and Pleistocene. Patterns of geographic and temporal diversification within the group were congruent with those uncovered for other co-distributed organisms. Independent paleoecological and geological data suggest that vicariance associated with climatic oscillations and neotectonic activity may have driven lineage divergence within the P. burmeisteri group. P. tetraploidea probably originated from polyploidization of P. distincta or from a common ancestor. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Amphibian; Brazilian Atlantic Forest; Hylidae; Phyllomedusa; Neotropics mtDNA; nDNA; Multilocus species tree; Phylogeny; Polyploidy